The job dispatch control policy for production lines with queue time constraints in semiconductor wafer fabrication - Lu, Lin (Nanyang Technological University, 2020)
The production lines become more and more complex with increasing demands from mass production to customised production. In the semiconductor fab, there are many recipes which requires different processes and different priorities. In addition, overlapped time window constraints and product mix make it more difficult to manage production lines.Thus, the application of queueing theory becomes extremely important to improve efficiency of the factory. A practical control theory is necessary to be used for engineers to manage products more efficiently and automatically. In this report, two methods are studied to develop the control policy for the production line with product mix and overlapped time constraints. The first method is to directly calculate the accurate cycle time using the formula we developed for each kind of product of the original queuing system. The second method uses reduction method to simplify the original queueing system so as to decrease the computation time. This article is organized as follows: Section 2 reviews the literature in this ﬁeld. Section 3 provides theorems for developing approximations and calculations of the waiting time and the cycle time. Section 4 gives the simulation validation. Finally, conclusions are drawn in Section 5.